The role of N6‐methyladenosine modification on diapause in silkworm (Bombyx mori) strains that exhibit different voltinism. Issue 12 (14th October 2019) - Jiang, Tao; Li, Jiashuang; Qian, Ping; Xue, Peng; Xu, Jin; Chen, Yanrong; Zhu, Juan; Tang, Shunming; Zhao, Qiaoling; Qian, Heying; Shen, Xingjia
Abstract: N6 ‐methyladenosine (m 6 A) plays a key role in regulating gene expression in myriad organisms. Diapause is an important plastic phenotype that allows insects to survive under specific environmental conditions. However, the diapause molecular mechanism remains unknown. In this study, we analyzed the phylogenetics of genes related to the m 6 A modification complex in the silkworm ( Bombyx mori ) based on identified sequences from other organisms. We detected the expression of these genes during different developmental phases from four strains with different voltinism. We also determined total m 6 A content in cells treated with different diapause hormone concentrations or eggs exposed to hydrochloric acid. Our data revealed that m 6 A‐modification‐related gene expression and m 6 A content were greater in diapause‐destinated compared to nondiapause‐destined strains. Our findings suggest that m 6 A modification may provide significant epigenetic regulation of diapause‐related genes in the silkworm. Abstract : N6‐methyladenosine (m 6 A)‐modification‐related gene expression and m 6 A content were greater in diapause‐destinated compared to nondiapause‐destined strains. Our findings suggest that m 6 A modification may provide significant epigenetic regulation of diapause‐related genes in the silkworm.